The Implementation of Scientific Approach With Project-based learning in Teaching Recount Text - Setyarini, Maria Niken (Universitas Negeri Semarang, 2018)
Teaching process in curriculum 2013 focuses on students centered learning, it means that students are active in teaching and learning process using scientific approach. One of the methods which is suitable with scientific approach is Project- based learning. In project-based learning, students have to finish project related to the learning material so the learning process will be meaningful because the students do and apply the learning material directly in their daily life. The objective of this study was to describe the implementation of scientific approach with project-based learning in teaching recount text. This study was a descriptive qualitative method based on the classroom observation. The problem investigated was how teachers implement scientific approach with project-based learning in teaching recount text. The subjects were 3 English teachers of SMAN 4 Semarang. The result showed that there was integration of scientific approach with project-based learning in teaching recount text, which was the procedures of scientific approach were in line with project-based learning. Two of three teachers had prepared syllabus, lesson plan, learning material, and learning media which appropriate with scientific approach. However it was also found that there were teachers who still hesitated in implementing scientific approach with project –based learning. It was showed from the unclear steps of scientific approach applied by the teachers.